Addressing underserved populations in autism spectrum research : an intersectional approach - Bennett, Matthew; Goodall, Emma (Emerald Publishing Limited, 2022)
When confronted with the large amount of research about the autism spectrum one can be forgiven for believing that every conceivable aspect has been studied. However, despite the abundance of research, there still remains several autism topics that are not yet comprehensively understood. Addressing Underserved Populations in Autism Spectrum Research: An Intersectional Approach highlights five areas of autism spectrum research that currently lack a substantial body of literature. These include, autistic seniors, autistic women, fathers raising autistic children, autistics with intellectual disabilities, and autistics from ethnic minorities. Bennett and Goodall explore each area, offering explanations for why they have been overlooked in the existing literature and recommendations and strategies for further research to help us better understand these parts of the autistic community. They also explore and address systemic racism within the autism research community and explain strategies that scholars can use to conduct research that is both respectful of autistics and methodologically rigorous. Readers will gain an understanding of some of the gaps in our knowledge about the autism spectrum and will obtain the tools needed to conduct robust and appropriate research that addresses these gaps.